СПОСІБ БУЖУВАННЯ СТРИКТУРИ СЕЧІВНИКА - V. І. Gorovyi; О. G. Коstyuk; V. М. Аndriychuk; S. P. Dmytryshyn; О. М. Каpshuk; О. L. Коbzin; О. V. Gorovyi (Клінічна хірургія)
СПОСІБ БУЖУВАННЯ СТРИКТУРИ СЕЧІВНИКА